Concurrent remission of lymphoma and Sjögren’s disease following anti-CD19 chimeric antigen receptor-T cell therapy for diffuse large B-cell lymphoma: a case report - Sheng, Lingshuang; Zhang, Yilun; Song, Qi; Jiang, Xufeng; Cao, Weiguo; Li, Lei; Yi, Hongmei; Weng, Xiangqin; Chen, Sheng; Wang, Zhongmin; Wu, Wen; Wang, Li; et al. (Frontiers in Immunology, 2023)
Anti-CD19 chimeric antigen receptor (CAR)-T cells not only target CD19-positive malignant lymphoma cells but also normal B cells. The utility of CAR-T cell therapy has been reported in rheumatoid arthritis and systemic lupus erythematosus; however, its use in Sjögren’s disease (SjD) remains unknown. In this study, we describe the case of a 76-year-old woman with active SjD for 10 years who was diagnosed with diffuse large B-cell lymphoma. After receiving anti-CD19 CAR-T cell therapy, she achieved complete remission (CR) on day 28. Since the onset of her 10-year history with SjD, she was negative for antinuclear antibodies and anti-Ro-52 for the first time on day 90 after CAR-T cell therapy. Six months after CAR-T cell therapy, the CR status was maintained, serum cytokine levels returned to their normal levels, and dry mouth symptoms improved. The EULAR Sjögren’s Syndrome Disease Activity Index score decreased from 5 to 2, indicating a partial remission of SjD activity compared with that before CAR-T cell treatment. In the early stage of treatment, she presented with grade 2 cytokine release syndrome and grade 1 neurotoxicity, which were completely controlled after an active intervention. This case highlights the potential application of CAR-T cells in treating autoimmune diseases, such as SjD.